EDUKASI PENANGANAN KATARSIS DAN TERAPI EMOSI PADAREMAJA PUTRI DUSUN TANON KLUPUTAN, DESA KENAIBAN, JUWIRING, KLATEN, JAWA TENGAH - Siti Hapsah Isfardiyana (Asian Journal of Innovation and Entrepreneurship, 2014)
Cathartic is an expression and release repressed emotions. Teenagers have theaggressiveness, energy and especially emotionally unstable, necessarily have a highvulnerability whenthey can’tmanage itwell andcanheadedtowards the wrong. Oftenly,emotions has negativeconnotations and it certainly caused some people argued thatemotion should be buried, but it is wrong path. Emotions were reasonably likely to bechanneled properly. This educational program is aimed at young women of TanonKluputanvillagewho still hold the view that emotion should be buried. The program iscarried out in 12 meetings that contain sharing, delivery of content or knowledge, andquestion and answeractivity that aims to provide knowledge and introduction to theteens about the dangers and cathartic along with media handling, one of which is writing.